The relationship between project governance mechanisms and project success: An international data set. Issue 7 (22nd July 2019) - Young, Raymond; Chen, Wenxin; Quazi, Ali; Parry, Warren; Wong, Adrian; Poon, Simon K.
Abstract : Purpose: Project governance has been linked to project success because top management support is necessary for projects to succeed. However, top managers are time poor and it is not clear which project governance mechanisms are effective for project success. The purpose of this paper is to address this issue and identify project governance mechanisms that correlate with success. Design/methodology/approach: This is a quantitative study. A theoretical model of project governance was developed and tested with secondary industry data gathered from 51 global organisations and 66, 817 responses. Findings: The results found five project governance mechanisms (Vision, Change, Sponsor, KPI and Monitor) significantly correlate with project success and are effective at different stages in the project lifecycle. Originality/value: Earlier research has found a relationship between project governance and project success but it has not been specific enough to guide top managers in practice. This is the first research to take this next step and identify project governance mechanisms that correlate with project success. One finding of this research that has particular value is the identification of when in the project lifecycle a particular governance mechanism is most effective.